EFEKTIVITAS PENERAPAN MODEL PEMBELAJARAN COLLABORATIVE LEARNING DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN EKONOMI - Cindy Alfira; Muhammad Yani; Syamsuria (Lembaga Berugak Baca, 2024)
This research is a quantitative study aimed at determining the effectiveness of implementing the Collaborative Learning model in improving student learning outcomes. The research uses a One group pre-test and post-test design. The population in this study was all students of Grade X at SMA Negeri 18 Bone, and the sample was Grade X 6, selected using purposive sampling technique. Data were obtained from student learning outcome tests in the form of pre-tests and post-tests. Data analysis used the paired sample t-test with the assistance of SPSS version 26. Referring to the average values in the pre-experimental class, the average student learning outcomes were obtained, with an average pre-test score of 46.91 and after the treatment (post-test) it increased to only 91.22. Due to the implementation of the Collaborative Learning model, students were able to provide simple explanations, improve basic skills, draw conclusions, and strategically plan and execute. From the normalized gain test results (N-Gain), a mean value of 0.8686 was obtained. This indicates that the Collaborative Learning model has an influence in improving student learning outcomes in the subject of economics. The Collaborative Learning model has proven to be effective in enhancing student learning outcomes in economics subject.